Patient satisfaction and oral health‐related quality of life after treatment with traditional and simplified protocols for complete denture construction. (21st October 2013) - Nuñez, Margaret C. O.; Silva, Donizete C.; Barcelos, Bento A.; Leles, Cláudio R.
Abstract : Objectives: The objective of this randomised controlled clinical trial study was to compare the effectiveness of a traditional and a simplified protocol for construction of conventional CD. Background: The replacement of conventional dentures can result in potential functional and aesthetic benefits to the patient. Previous studies suggest that simplified procedures for complete dentures (CD) construction achieve results similar to the traditional methods. Materials and Methods: Fifty patients were randomly divided into two equal groups, traditional protocol (T group) and simplified protocol (S group). Treatment outcomes were assessed before the insertion of the new dentures and 30 days and 6 months after the last adjustment. It included measurements of quality of life related to oral conditions measured by the Brazilian version of OHIP‐Edentulous scale and patients' satisfaction with the upper and lower dentures using a visual analogue scale (VAS), which combines the patient's perception in relation to overall satisfaction with the comfort, stability, ability to chew, ability to talk and aesthetics. Results: The results showed significant reduction in negative impacts of oral conditions on quality of life and improved satisfaction with the upper and lower dentures ( p < 0.001) at the 30‐day and 6‐month follow‐up. Quality of life improvement occurred in all dimensions of the OHIP‐Edentulous ( p < 0.001). Despite the significant reduction in quality of life impacts and significant increase in patients' satisfaction with the dentures, there were no differences between the traditional and simplified protocols ( p > 0.05). Conclusions: It was concluded that the simplified protocol results in patent's perception of treatment outcomes similar to the traditional protocol.